Motivating and supporting young people to study mathematics: A London perspective (UCL Press, 2014)
This paper explores which classroom and teacher factors are associated with post-16 mathematics aspirations, mathematics intrinsic motivation, and mathematics self-concept. Few studies explore all three outcomes among the same set of students or make linkages across the factors that are important to these outcomes. The analysis is based on the survey responses of 761 Year 8 (age 13) and 715 Year 10 (age 15) students from 17 London schools as learners of mathematics. The analysis indicates that teaching for engagement is important for intrinsic mathematics motivation but not for future mathematics aspirations. In addition, students' emotional responses to mathematics lessons are important for their mathematics self-concept but not for future mathematics aspirations. Advice-pressure to continue with mathematics post-16, extrinsic material gain motivation, and mathematics self-concept underpin mathematics aspirations (even after controlling for the support students received from their families in mathematics attainment). The gender difference within mathematics self-concept among these young Londoners was higher than that found across England, although there were substantially fewer gender differences in relation to questions that explored students' perceptions of their mathematics lessons and teachers. The article concludes with some suggestions for both national and London policymakers because the study of mathematics is seen as of considerable importance to both young people and the economic life of the capital.